The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2010
DOI: 10.1103/physrevlett.104.185003
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Confined Current Ribbon in JET Plasmas

Abstract: We report the identification of a localized current structure inside the JET plasma. It is a field-aligned closed helical ribbon, carrying current in the same direction as the background current profile (cocurrent), rotating toroidally with the ion velocity (corotating). It appears to be located at a flat spot in the plasma pressure profile, at the top of the pedestal. The structure appears spontaneously in low density, high rotation plasmas, and can last up to 1.4 s, a time comparable to a local resistive tim… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(60 citation statements)
references
References 18 publications
3
57
0
Order By: Relevance
“…We have concentrated our efforts in the domain where J BS at the edge is large, which tends to coincide with the region where low n = 1 structures dominate (corresponding to the upper half of the graph in figure 8). In our opinion, these structures constitute a very realistic model for the OM observed on JET (Solano 2010) and the EHO detected on DIII-D and other tokamaks (Burrell et al 2005;Suttrop et al 2005;Hu et al 2015). A detailed analysis of the equilibrium state for large edge J BS indicates that a parallel helical current density ribbon forms just outside the q = 3 rational surface with a radial extent that aligns with the vanishing magnetic shear region associated with the flat spot in the q-profile caused by the bootstrap current.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have concentrated our efforts in the domain where J BS at the edge is large, which tends to coincide with the region where low n = 1 structures dominate (corresponding to the upper half of the graph in figure 8). In our opinion, these structures constitute a very realistic model for the OM observed on JET (Solano 2010) and the EHO detected on DIII-D and other tokamaks (Burrell et al 2005;Suttrop et al 2005;Hu et al 2015). A detailed analysis of the equilibrium state for large edge J BS indicates that a parallel helical current density ribbon forms just outside the q = 3 rational surface with a radial extent that aligns with the vanishing magnetic shear region associated with the flat spot in the q-profile caused by the bootstrap current.…”
Section: Discussionmentioning
confidence: 99%
“…We interpret these deformations as indicative of the development of an external kink/peeling mode that saturates at finite amplitude. The distortions observed are symptomatic of the edge harmonic oscillation (EHO) (Burrell et al 2005) first reported on DIII-D, but subsequently observed on many other machines (Suttrop et al 2005;Hu et al 2015), and the outer mode (OM) measured on JET (Solano et al 2010). The shape of the last closed magnetic flux surface on TCV at four different cross-sections projected onto a single toroidal plane for β N = 1, 1.49, 1.99 and 2.47 are presented in figure 4.…”
Section: -D Equilibrium Numerical Simulations: Nonlinearly Stable Stmentioning
confidence: 99%
“…It is possible that ambipolar electron particle flux is responsible for extremely good plasma confinement in snakes or current filament. [22][23][24][25] The electron particle flux is…”
Section: Kinematic Effects Of Parallel Mass Flowmentioning
confidence: 99%
“…Using Eqs. (25) and (26) and changing independent variables from w; h; E; l ð Þto p f ; h; E; l ð Þ , we recast Eq. (A1) as…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…ELMs deposit large, localized and impulsive heat loads that can damage the divertor. A quiescent regime with edge harmonic oscillations (EHO) or broadband MHD activity is observed in some DIII-D [4][5][6][7][8][9][10][11], JT-60U [12,13], JET [14] and ASDEX-U [15], discharge scenarios. These ELM-free discharges have the pedestal-plasma confinement necessary for burning-plasma operation in ITER [11].…”
Section: Introductionmentioning
confidence: 99%